Demeter in Hellenistic poetry: religion and poetics - Constantinou, Maria (The University of Edinburgh, 2014)
The thesis examines the presence of Demeter in Hellenistic poetry, while it also considers the way contemporary Demeter cult informs the poetic image of the goddess. My research focuses on certain poems in which Demeter is in the foreground, that is, Philitas’ Demeter, Callimachus’ Hymn to Demeter, Theocritus’ Idyll 7, and Philicus’ Hymn to Demeter, supplemented by the epilogue of Callimachus’ Hymn to Apollo and Philicus’ Hymn to Demeter. The first part of my study is dedicated to the presentation of the evidence for Demeter’s role in the religious life of places that are directly or indirectly associated with the poems I discuss, that is, Egypt, Cyrene, Cos and Cnidus, in order to establish the cultic and historical framework within which Demeter’s literary figure appears. In the second part I closely examine the poems that feature Demeter and conclude that the goddess and motifs closely linked with her have poetological significance, which supports the view that Demeter functions as a symbol of poetics. Furthermore, I examine the social elements in the narrative of the most extant Hellenistic poem on Demeter, i.e. Callimachus’ Hymn to Demeter, and propose that these reflect Demeter’s role as a ‘social’ goddess.
Keywords: Hellenistic poetry; Demeter cult